2018
DOI: 10.1002/jper.17-0753
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiotensin II receptor I prevents inflammation and bone loss in periodontitis

Abstract: Our studies show a central role for Ang II as a pro-inflammatory Toll-like receptor mediator in the pathogenesis of PH-exacerbated periodontitis, indicating that Ang II may be a reasonable target in patients with PH and periodontitis comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
(81 reference statements)
2
12
0
Order By: Relevance
“…Our previous and current results showed that Ang II increased in lesion area (Appendix Fig. 7A) and augmented the inflammatory response both in vivo and in vitro (Li et al 2019). We also analyzed the LPS receptor (TLR4) and Ang II receptor (AT1R) in vivo.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Our previous and current results showed that Ang II increased in lesion area (Appendix Fig. 7A) and augmented the inflammatory response both in vivo and in vitro (Li et al 2019). We also analyzed the LPS receptor (TLR4) and Ang II receptor (AT1R) in vivo.…”
Section: Discussionsupporting
confidence: 57%
“…Four-week-old Nos3 -/- mice were acquired from the Model Animal Research Center of Nanjing University for mating and breeding; these mice showed spontaneous hypertension (de Jonge et al 2002; Li et al 2004) and upregulation of Ang II (Li et al 2019). Eight-week-old female mice were divided into 8 groups for the experiment:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these metabolites are known to be increased in the circulation of tobacco smokers and also involved in periodontal disease development. 31,32 Further, pentosidine, a marker of advance glycation end products, was higher in the ENDS user group (3.19 fold) (Table 2). Advanced glycation end products are known to be involved in tobacco-induced inflammation and the development of periodontal disease.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, recent studies have shown that RAS blockers are able to reduce the inflammation and, therefore, decrease the expression of matrix metalloproteinases (MMPs) in RANK/RANKL axis and cathepsin K in a rat model of PD (Araújo et al, 2013). Furthermore, our knowledge about this concept is growing due to increase in the number of studies that have described treatment of mice with ACE inhibitor preventing bone loss Gonçalves-Zillo et al (2013), the protective effect of ACE inhibitors in PD-induced and arthritis-associated alveolar bone loss (Queiroz-Junior et al, 2015), and the mechanism by which AT1R inhibitor prevents inflammation and alveolar bone loss in periodontitis (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%